Regenerative Protocol for Defects of the Plantar Fascia: A Case Series - Parker, Robert; Shou, John; Woods, Crislyn; Lambert, Naomi; Barrett, Tyler (Archives of Clinical and Biomedical Research, 2025)
Foot pain related to the plantar fascia is common in adults regardless of athletic background. Many pathologies can lead to the diagnosis of plantar enthesopathy, but the most relevant to this case series is related to structural defects within the plantar fascia. Due to the variety and sometimes unclear etiology of plantar fasciosis, no single standard of care treatment protocol is recognized. Often, patients receive NSAIDs, night splints, taping, physical therapy, foot orthosis, and extracorporeal shock wave therapies. This study presents Wharton Jelly (WJ) tissue allografts as an additional intervention in a regenerative protocol for patients who fail standard-care treatments. WJ allografts are applied to supplement connective tissue defects directly, unlike other therapies, which aim to reduce swelling and symptomatic pain. This observational study includes seven patients who have previously failed standard-of-care treatment. Each received extracorporeal pulse-activated therapy (EPAT), WJ, class four laser therapy, and an orthotic. Patient progress was tracked using a visual analog scale, 0-10 scoring, reported by the patient at the initial visit and approximately thirteen weeks following, reporting an average improvement of 50% with significant differences in initial and final scores. The study's limitations include a small cohort size and a nonblinded observational design. These promising results provide evidence for a more extensive, randomized study to define dosage protocols further and confirm safety and efficacy.